Preliminary design for UP Diliman bikeways network extension - Villanueva, Dana Angelica R.; Duot, Ruby Jane M.; Sigua, Ricardo G. (Quezon City College of Engineering, University of the Philippines Diliman, 2015)
As an inexpensive and efficient trip mode, cycling has been actively promoted as a sustainable mode of transport in many cities around the world. This study aims to design a bikeway network system in UP Diliman, more specifically to extend the existing bikeway to accommodate regions of the campus with high potential demand. The study collected data on origin and destination demand and bicycle trip characteristics in order to identify the suitable routes for this network. It has been found out that only a small percentage of the daily trips made within the university were made by bicycles. Also, he demand for bike traverse is high from north to south of the campus, which is mainly from the residence halls to the College of Science Complex. This study will also present various ways in promoting bicycle as an alternative mode of transportation in the campus through extensive educational programs.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Bicycle lanes; Bicycle trails